CURRENT CHALLENGES IN ENSURING INTERNATIONAL AND NATIONAL SECURITY - Naumik-Gladka, Kateryna G.; Ptashchenko Оlena V.; Imnadze, Irakliy N.; Rоzumnyy Оleksandr M. (Journal of Strategic Economic Research, 2022)
The article provides insights into the modern aspects and challenges of economic globalization that triggers a fundamental change in the world economic order, as well as demonstrates the emergence of a new global economic culture, a new type of economic consciousness and a new type of international relations. In this context, exploring globalization processes and identifying their patterns seems especially relevant. The study reveals that within on-going globalization settings, the scale of international economic relations demonstrates a rapidly growing trend, the number of their immediate participants is increasing, the forms of these relationships are being updated and getting more complicated. It is observed that in the vulnerable market economic environment with intensified international competition there are more and more common issues to be addressed by joint efforts in searching for effective solutions, moreover, there are certain conflicts arising that can be resolved only at the regional and multilateral levels. A special emphasis is put on the need to integrate collective efforts of international organizations and forums through economic diplomacy which will contribute to finding the best compromise between governments to meet the interests of all or most of stakeholders in the world community, for many countries this will mean to benefit from international mechanisms and procedures, and reducing adverse effects from TNC activities to engross the advantages of globalization. The study findings have verified that from international economic relations perspectives, among fundamental reasons behind business globalization are the advances in computer and communication technology which exchanging of ideas and information between different countries, expand consumer awareness of foreign-made products. The study also demonstrates how cable systems in Europe and Asia facilitate firms in many countries to shape simultaneously both regional and sometimes global demand, and global communication networks allow them coordinating production and aligning common goals worldwide while companies located in different parts of the world produce the same end product. It is argued that reducing customs barriers to investment and trade by the vast majority of governments proves effective in launching in new markets for international export companies that offer opportunities and capacities for local producers. Apart from the above, the study has traced a trend towards unification and socialization of the global community. In particular, it is observed that continuous changes in the governance paradigm as well as in the international environment impose an integrated effect upon social, political and mental aspects of national interests. It is concluded that building a conceptual framework of national and international interests is a complex and long-term process influenced by geopolitical, economic, socio-cultural and psychological factors, being adjusted through the system of social values and reflected in research studies and manifestations of collective consciousness. From this perspective, the key aspects of national and international security have been explored.